A bilineage thermosensitive hydrogel system for stimulation of mesenchymal stem cell differentiation and enhancement of osteochondral regeneration. (15th March 2022) - Lin, Tzu-Hsiang; Wang, Hsueh-Chun; Wu, Meng-Chian; Hsu, Horng-Chaung; Yeh, Ming-Long
Abstract: Osteochondral lesions in weight-bearing joints often fail to heal due to their poor intrinsic repair capacity and may lead to severe complications such as osteoarthritis. This study investigated the chondrogenesis, osteogenesis, and regenerative potential of an injectable, thermoresponsive chitosan-graft-poly(N-isopropylacrylamide) (CS-g–PNIPAAm, or CSPN) hydrogel combined with infrapatellar fat pad-derived mesenchymal stem cell (IFPSC) and platelet-rich plasma (PRP) with regard to osteochondral regeneration. CSPN hydrogels were prepared and characterized using several procedures. Optimal CSPN hydrogel (CSPN hydrogel with 67% of PNIPAAm, or CSPN05) was examined following a biochemical assay and animal implantation. PRP incorporated CSPN05 hydrogel, CSPN05-PRP, was fabricated. We found that rabbit IFPSCs (rIFPSCs) cultured in the CSPN05-PRP hydrogel (rIFPSC–CSPN05–PRP) enhanced the expression of chondrogenic and osteogenic genes after 1, 3, 5, and 7 days of culture and significantly increased sulfated glycosaminoglycan content, alkaline phosphatase activity, and mineralization after 5 and 7 days of culture compared with PN and CSPN05. In addition, PRP induced the expression of specific signaling molecules for chondrogenesis and osteogenesis in its signaling pathway. A preliminary in vivo study showed that rIFPSC-CSPN05–PRP could effectively regenerate the osteochondral defect at 4 weeks. Thus, the combination of IFPSC, the CSPN hydrogel, and PRP can synergistically enhance chondrogenic and osteogenic gene expression, cartilage- and bone-specific extracellular matrix production, hyaline cartilage regeneration, and mineralized osseous tissue formation. CSPN scaffolds with PRP show potential as biomaterial by providing mechanical support for cell growth and inducing stem cells to differentiate into osteochondral lineages for application in regenerative medicine. Graphical abstract: Image 1